Injectable hydrogel as well as preparation method and application thereof

By using magnesium acrylate, carboxymethyl chitosan and phytic acid to construct chemical-physical crosslinked dual network hydrogels, the problem of degradation of the adhesion ability of existing medical adhesives in wet environments is solved, and long-term stable adhesion and high-strength adhesion effects are achieved.

CN119552389AActive Publication Date: 2025-03-04SOUTHEAST UNIV +1

Patent Information

Application Number
CN202411475276.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-03-04
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The adhesion ability of existing medical adhesives in long-term wet environments has been greatly reduced, making it difficult to achieve long-term and stable adhesion in physiological environments.

Method used

A blended solution with magnesium acrylate, carboxymethyl chitosan and phytic acid as the main components is constructed to construct a chemical-physical cross-linking dual network hydrogel. Through covalent cross-linking and non-covalent cross-linking mechanisms, a stable polymer network is formed to enhance the bonding ability of the adhesion interface.

Benefits of technology

The long-term and stable adhesion ability of hydrogel adhesive in the physiological environment is achieved, which significantly improves the adhesion effect in wet environments, and improves structural strength and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552389A_ABST
    Figure CN119552389A_ABST
Patent Text Reader

Abstract

The invention discloses injectable hydrogel as well as a preparation method and application thereof. The hydrogel is a chemical-physical double-network cross-linked hydrogel prepared from a blended solution with magnesium acrylate, carboxymethyl chitosan and phytic acid as main components. Wherein covalent cross-linking is derived from a magnesium polyacrylate network constructed by free radical polymerization reaction. Non-covalent cross-linking is derived from hydrogen bonds and electrostatic interaction among components in an interpenetrating network and a carboxymethyl chitosan chain entanglement network formed by gradual induction in the application process of a physiological environment. In the preparation process, the pH value of a reaction system is controlled by controlling the concentration of phytic acid, magnesium ions are chelated, then the structural strength of the hydrogel is controlled, and the injectable effect is achieved. Meanwhile, phytic acid can be chelated with protein, so that the adhesion of the phytic acid to tissues is enhanced. The preparation process is simple and convenient, easy to control and suitable for large-scale industrial production, and all the raw materials are easy to obtain and low in price. The hydrogel has high adhesion efficiency and wet adhesion strength to tissue.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of an injectable hydrogel suitable for continuous adhesion in a physiological environment, belonging to the technical field of medical adhesive preparations. Background Art

[0002] As a type of adhesive material with soft material properties, hydrogel adhesives play a key role in a wide range of wet environment applications, including underwater industrial repair and mechanical movement, tissue adhesion and sealing in physiological environments, etc. Compared with adhesives that exhibit viscoelastic liquid behavior, hydrogel adhesives can provide better modulus matching and transmission performance with the substrate. Most traditional tough hydrogels have poor adhesion due to the lack of polymer interface anchoring between the substrate surface or the destruction of the interface interaction by the hydration layer. This disadvantage is particularly obvious when the hydrogel adhesive is directly applied in a wet environment or after long-term application. In order to solve the above problems, the synergistic effect of the following two effects is required. On the one hand, the low hydration swelling of the hydrogel matrix should be ensured, making it difficult to suffer from hydration damage, thereby presenting long-term stable mechanical properties. On the other hand, when directly applied in a wet environment, the interfacial hydration layer must be removed through strategies such as the polymer network or surface micropatterning of the hydrogel adhesive, and covalent bonding must be established at the adhesion interface.

[0003] Magnesium acrylate, which has rich functional carboxyl groups as multiple binding sites and strong adhesion energy, has been widely used in the field of industrial adhesives. It is very attractive to choose magnesium acrylate as the main component of hydrogel. However, the underwater long-term adhesion effect of magnesium polyacrylate (PAMg) single network hydrogel is not ideal. Therefore, the physical network of non-covalent cross-linking is sought, and the physical-chemical double network gel with "sacrificial bond" theory is constructed in combination with magnesium polyacrylate. As a kind of double-reinforced polymer network material, it provides the possibility to maintain or even enhance the mechanical properties of adhesive materials used in wet environments for a long time. Chitosan (CS) is the only alkaline polysaccharide discovered so far that is both biocompatible and biodegradable. After simple treatment in a monovalent anionic salt solution, a chain entanglement network can be generated. The positively charged N-glucosamine units in the CS chain attract the excess Cl-, thereby reducing the electrostatic repulsion between the N-glucosamine units, which leads to the entanglement of the CS chain and the volume shrinkage of the system. Summary of the invention

[0004] Purpose of the invention: In view of the defect that the adhesion ability of existing medical adhesives is greatly reduced in a long-term wet environment, the purpose of the present invention is to provide an injectable hydrogel, a preparation method and its application. A chemical-physical cross-linked double network hydrogel is prepared from a blended solution of magnesium acrylate, carboxymethyl chitosan (CMCS) and phytic acid (PA) as the main components as an adhesive material. The covalent cross-linking is derived from the polyacrylic acid network constructed by free radical polymerization, and the non-covalent cross-linking is derived from the hydrogen bonds and electrostatic interactions between the components in the interpenetrating network, and the carboxymethyl chitosan chain entanglement network gradually induced by the salting-out effect, the shielded electrostatic repulsion and the enhanced hydrophobic chain interaction during the application process in the physiological environment. In addition, the strong chelating ability of phytic acid contained in the gel can form a more stable electrovalent bond with protein. The long-term stable adhesion ability of the hydrogel adhesive in the physiological environment can be achieved by synergizing the dissipative matrix that is not easily affected by swelling and the multi-bonded adhesion interface.

[0005] Technical solution: In order to achieve the above purpose, the present invention adopts the following technical solution: An injectable hydrogel is a chemically-physically cross-linked double network hydrogel constructed with a blend solution of magnesium acrylate, carboxymethyl chitosan and phytic acid as main components, wherein the covalent cross-links are derived from a polyacrylic acid network constructed by a free radical polymerization reaction, and the non-covalent cross-links are derived from hydrogen bonds and electrostatic interactions between components in the interpenetrating network, as well as a carboxymethyl chitosan chain entanglement network gradually induced to form due to the salting-out effect, shielded electrostatic repulsion and enhanced hydrophobic chain interactions during application in a physiological environment; phytic acid forms a more stable electrovalent bond with protein by virtue of its strong chelating ability; the synergistic dissipative matrix that is not easily affected by swelling and the multi-bonded adhesion interface can realize the long-term stable adhesion ability of the hydrogel adhesive in a physiological environment.

[0006] The present invention provides a method for preparing an injectable hydrogel, comprising the following steps: Step 1: Disperse magnesium hydroxide powder in deionized water, and then add acrylic acid solution to prepare a 10-50 wt% magnesium acrylate solution.

[0007] Step 2: Dissolve the carboxymethyl chitosan powder and the prepared cross-linking agent solution in the aqueous solution of step 1, stir well to prepare a carboxymethyl chitosan-cross-linking agent-magnesium acrylate aqueous solution.

[0008] The degree of substitution of carboxymethyl chitosan is ≥80%, and the concentration is 1.0~5.0wt%; the cross-linking agent is N, N'-methylenebisacrylamide (MBAm), the solution concentration is 20mg / mL, and the volume ratio of the cross-linking agent solution to the acrylic acid monomer is 0~1:8 and greater than 0.

[0009] Step 3: Add 0-50 wt% phytic acid solution (greater than 0 wt%) dropwise into the solution prepared in the above step 2, stir for 10-40 minutes, and prepare a precursor solution of hydrogel. The mechanical strength of the hydrogel is regulated by adjusting the amount of phytic acid added.

[0010] Step 4: Heat the precursor solution of the gel described in step 3 in a water bath, add the prepared initiator solution (the initiator is ammonium persulfate) dropwise, raise the temperature to 50-70°C, then continue stirring for 10-40 minutes to evenly disperse the components in the solution, and wait for the polymerization to be completed.

[0011] The application of the obtained injectable hydrogel as a rapid hemostatic material is to directly adhere the hydrogel to the surface of bleeding tissue, so as to obtain a hydrogel-tissue adhesion interface that can last in a physiological environment. In one embodiment, the bleeding is liver bleeding, and the hydrogel is directly adhered to the surface of the bleeding tissue.

[0012] The principle of the present invention is as follows: In order to break through the barrier of hydration destruction, actively and effectively utilize the saline solution of the physiological environment, improve its solubility, and increase the injectability of the gel, the inventor replaced the hydroxyl group on the chitosan with a carboxyl group to obtain carboxymethyl chitosan, which has the advantages of better blood coagulation and reduced scar formation. The construction of magnesium polyacrylate-carboxymethyl chitosan hybrid hydrogel can provide significant advantages for the wet adhesion of the hydrogel. In order to further enhance the adhesion strength of the double network hydrogel matrix, phytic acid (PA) is selected to be introduced. Phytic acid is composed of six identical phosphate groups on the inositol ring. PA contains a large amount of electronegative oxygen and has a strong electronegativity, which can easily bind to -NH on the tissue. 2 Reaction to form a stable electrovalent bond to prevent degradation; phytic acid has strong chelating properties and is easy to react with Mg 2+ , Ca 2+ Divalent cations such as Fe 3+ The phytic acid content is adjusted to control the pH value of the solution and the phytic acid content is adjusted to control the phytic acid content in the solution. 2+ The coordination formation of magnesium phytate controls its structural strength. And because it easily chelates Fe 3+ and proteins, which are more conducive to promoting hemostasis and enhancing its adhesion properties. In summary, the synergistic dissipative matrix that is not affected by swelling and the multi-bonded adhesion interface can achieve the injectability of the hydrogel and the long-term stable adhesion ability in a physiological environment. Beneficial Effects

[0013] 1. The hydrogel matrix prepared by the present invention can achieve rapid, high-strength and repeatable adhesion to different surfaces (including engineered solids and tissues) in a dry and physiological environment.

[0014] 2. The introduction of phytic acid into the adhesion interface can significantly improve the wet environment (underwater) adhesion ability of the hydrogel adhesive. The synergistic dissipative matrix that is not easily affected by swelling and the multi-bonded adhesion interface can achieve long-term stable adhesion of the hydrogel adhesive in a physiological environment.

[0015] 3. In the hydrogel matrix prepared by the present invention, the synergistic effect of phytic acid and carboxymethyl chitosan can improve the structural strength and mechanical properties of the product, so that it can adapt to more application environments.

[0016] 4. The hydrogel matrix prepared by the present invention achieves high bursting pressure on various tissue surfaces in air and simulated physiological environments. In addition, it has a significant rapid hemostatic effect on the rat in vitro liver bleeding model.

[0017] 5. The hydrogel prepared by the present invention has readily available raw materials and can be prepared by in-situ polymerization of a precursor solution and an initiator. The preparation process is simple and rapid, and is easy to operate, control and industrially produce on a large scale, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The adhesion tensile strength of the hydrogel matrix prepared in the embodiment of the present invention in a dry environment; the adhesion tensile strength can reach up to 132.8 kPa; wherein, (a) the effect of different crosslinker concentrations on the adhesion tensile properties of the product in Example 1; (b) the effect of carboxymethyl chitosan on the adhesion tensile properties of the product in Example 2; (c) the effect of phytic acid concentration on the mechanical properties of the product in Example 3; Figure 2 Rheological tests of hydrogels prepared from samples 1, 2, 3, 4, 6, 7, and 8 in Examples 1, 2, and 3 of the present invention; Figure 3 The hydrogel matrix (sample 2) prepared in Example 1 of the present invention was subjected to bursting pressure test after adhesion on different tissue surfaces: skin; Figure 4 The in vitro hemostatic effect of the hydrogel matrix (sample 3, sample 5, sample 7) prepared according to Example 1 of the present invention on the SD rat liver bleeding model. DETAILED DESCRIPTION

[0019] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.

[0020] Example 1: Effect of crosslinking agent concentration on product mechanical properties: (1) Dissolve 0.2 g of N, N'-methylenebisacrylamide in 10 mL of deionized water to prepare a crosslinker solution; dissolve 2 g of ammonium persulfate in 10 mL of deionized water to prepare an initiator solution.

[0021] (2) Disperse 0.9 g of magnesium hydroxide in 7.5 mL of deionized water; gradually add 2 mL of acrylic acid to react to obtain a magnesium acrylate solution.

[0022] (3) Add 0 and 100 μL of the crosslinker solution prepared in step (1) and 0.2 g of carboxymethyl chitosan to the magnesium acrylate solution in step (2), respectively, and stir thoroughly.

[0023] (4) Take 1.5 mL of 50 wt% phytic acid solution and add it dropwise to the solution of step (3), and stir it in a 50°C water bath for 30 min. Then add 500 μL of the initiator solution of step (1) dropwise, raise the temperature of the water bath to 65°C and continue heating and stirring until it is cured and cross-linked (obtaining samples 1 and 2).

[0024] The adhesion ability of the hydrogel matrix was evaluated according to the ASTM F2258 tensile test. Figure 1 a, it can be clearly seen that the crosslinking agent concentration significantly affects the crosslinking density of the hydrogel matrix. Sample 2 uses 100 μL of crosslinking agent solution and has a higher crosslinking density, thus having a higher adhesion tensile strength. Figure 2 As can be seen in a, sample 2 has a higher crosslinker concentration and a higher storage modulus G'. In addition, affected by the crosslinker concentration, the storage modulus G' of sample 1 changes more rapidly with the angular frequency ω at low frequencies (0-1rad / s), while at high angular frequencies, the material exhibits stronger elastic behavior. The increase in crosslinker concentration increases the rigidity of the entire system, so the storage modulus G' of sample 2 increases at medium and high frequencies, and the rate of change at this time tends to be gentle, because the elasticity of the crosslinked network dominates the response of the system.

[0025] Example 2: Effect of carboxymethyl chitosan on the mechanical properties of the product: (1) Dissolve 0.2 g of N, N'-methylenebisacrylamide in 10 mL of deionized water to prepare a crosslinker solution; dissolve 2 g of ammonium persulfate in 10 mL of deionized water to prepare an initiator solution (2) Disperse 0.9 g of magnesium hydroxide in 7.5 mL of deionized water; gradually add 2 mL of acrylic acid to react to obtain a magnesium acrylate solution.

[0026] (3) Add 100 μL of the cross-linking agent solution prepared in step (1), 0 g and 0.2 g of carboxymethyl chitosan respectively to the magnesium acrylate solution prepared in step (2), and stir thoroughly.

[0027] (4) 1.5 mL of 50 wt.% phytic acid solution was added dropwise to the solution of step (2) and stirred in a 50°C water bath for 30 min. Then 500 μL of the initiator solution of step (1) was added dropwise. The water bath was heated to 65°C and heated and stirred continuously until it was cured and cross-linked (Samples 3 and 4 were obtained).

[0028] The adhesion ability of the hydrogel matrix was evaluated according to the ASTM F2258 tensile test. Figure 1 b It can be seen that sample 4 with added carboxymethyl chitosan has better adhesion tensile strength. Figure 2 b It can be seen that sample 3 has a higher storage modulus G' at low angular frequency ω. For hydrogels without carboxymethyl chitosan, it may show a more stable physical cross-linked network in this area, or the interaction between its molecular chains is relatively close, so the elastic response is stronger and the storage modulus is higher. In the high frequency region, sample 4 contains carboxymethyl chitosan, has more cross-linking points and a higher cross-linking density, so it shows a higher storage modulus.

[0029] Example 3: Effect of phytic acid concentration on the mechanical properties of the product: (1) Dissolve 0.2 g of N, N'-methylenebisacrylamide in 10 mL of deionized water to prepare a crosslinker solution; dissolve 2 g of ammonium persulfate in 10 mL of deionized water to prepare an initiator solution.

[0030] (2) Disperse 0.9 g of magnesium hydroxide in 7.5 mL of deionized water; gradually add 2 mL of acrylic acid to react and obtain a magnesium acrylate solution.

[0031] (3) Add 100 μL of the cross-linker solution prepared in step (1) and 0.2 g of carboxymethyl chitosan to the magnesium acrylate solution prepared in step (2) and stir thoroughly.

[0032] (4) 0, 1.0 mL, 1.5, and 2 mL of a 50 wt% phytic acid solution were added dropwise to the solution of step (2), respectively, and stirred in a 50°C water bath for 30 min. Then, 500 μL of the initiator solution of step (1) was added dropwise. The water bath was heated to 65°C and heated and stirred continuously until it was cured and cross-linked (obtaining samples 5, 6, 7, and 8).

[0033] The adhesion ability of the hydrogel matrix was evaluated according to the ASTM F2258 tensile test. Figure 1 As can be seen from Figure c, as the concentration of phytic acid increases, the adhesion tensile strength of the sample decreases. Figure 2 c, it can be clearly seen that the phytic acid concentration significantly affects its crosslinking density. The samples with lower phytic acid concentration have higher storage modulus and show higher structural strength. Figure 2 It can be clearly seen in c that with the increase of phytic acid concentration, the storage modulus of the sample gradually decreases.

[0034] Among them, samples 2, 4, and 7 are samples of the same component. Example 4

[0035] The bursting pressure of the hydrogel (sample 2) prepared in Example 1 of the present invention after being attached to the skin surface of different tissues was measured by constructing an in vitro bursting pressure experimental device. The hydrogel (diameter 8 mm, thickness 2-3 mm) of Example 1 was directly blocked at the gap with a diameter of 2 mm on the tissue surface, and the device was immediately pressurized to record the peak pressure displayed when the hydrogel failed in adhesion or cohesion, which was the bursting pressure value. In a dry environment, the bursting pressure of sample 2 for the skin was 0.8 psi. The high bursting pressure exhibited by the hydrogel matrix prepared by the present invention expands its application potential in the field of medical sealants or occluders. Example 5

[0036] The in vitro hemostatic effect of the hydrogel prepared in the present invention was evaluated by constructing a liver injury and bleeding model in SD rats. Here, D rats (260-270 g) were anesthetized and fixed on a surgical board, and the surgical board was kept at an angle of 30° to the horizontal plane. The liver was exposed through an abdominal incision, and the excess slurry around the liver was carefully removed with sterile gauze. A pre-weighed qualitative filter paper was placed at the bottom of the liver, and a sealing film with a large enough area was placed at the bottom of the filter paper to prevent the tissue slurry from affecting the weight of the filter paper. Subsequently, liver bleeding was induced using scissors, and sample 3, sample 5, and sample 7 hydrogels were immediately injected or adhered to the bleeding site in situ, and the timing was started. The group without any treatment was used as a blank group. Pictures were recorded at 30s, 60s, 90s, and 120s, respectively. Finally, the recording was stopped at 120s, and the cumulative blood loss was recorded by weighing the weight gain of the filter paper. The figure shows the bleeding of a 1cm×1cm cross-shaped incision on the surface of the rat liver at 30s, 60s, 90s, and 120s, respectively. At 120s, the amount of bleeding was 0.0788g for the blank group, 0.0551g for sample 3, 0.0153g for sample 5, and 0.0249g for sample 7. The order of bleeding from large to small is blank group > sample 3 > sample 7 > sample 5. It can be seen that sample 5 has the best hemostatic effect, followed by sample 7, and the worst is sample 3. Although sample 5 without phytic acid has a better hemostatic effect, when phytic acid is not added, the wet environment adhesion effect is poor. Sample 7 with phytic acid added has a better wet adhesion effect and better hemostatic ability. Therefore, after balancing hemostasis and adhesion, the comprehensive effect of sample 7 with phytic acid added is the best.

[0037] The rapid hemostasis ability of the hydrogel obtained from sample 7 can be attributed to the wound closure under wet environment and the synergistic effect of the inherent hemostatic activity of carboxymethyl chitosan and the sealing of bleeding sites by magnesium polyacrylate-based hydrogel. The carboxyl groups on the surface of the hydrogel and the phosphate groups in phytic acid form non-covalent molecular bonds with the tissue surface, including hydrogen bonds, mutual electrostatic interactions, and coordination bonds, so that the hydrogel can quickly adhere to the bleeding site, seal the wound and promote hemostasis. At the same time, carboxymethyl chitosan can promote rapid aggregation of red blood cells by promoting the adhesion and aggregation of platelets, thereby promoting rapid hemostasis.

[0038] It can be seen that in the hydrogel matrix, whether carboxymethyl chitosan is contained greatly affects the hemostasis speed of the sample, but in the sample 5 containing only carboxymethyl chitosan, the adhesion effect of tissue and sample in the wet environment is not obvious. It is speculated here that it may be because the bond energy of hydrogen bond and electrostatic interaction is very low, and the water polarity in the blood is very strong, which will destroy the bond, resulting in the inability to adhere firmly in the wet environment. The adhesion effect is greatly improved in the sample 7 with phytic acid, and it can be firmly adhered to the bleeding wound. Compared with the control group containing carboxymethyl chitosan, the sample 3 with only magnesium acrylate and phytic acid has the highest adhesion effect, which may be due to the strong chelation of phytic acid and some amino reactions on carboxymethyl chitosan, reducing the phosphate group, so reducing the adhesion strength. However, in the sample 7 with carboxymethyl chitosan and phytic acid added, because of the hemostatic effect of carboxymethyl chitosan, the coagulation of the wound can be promoted, so the total bleeding volume is less. At the same time, adding phytic acid in the sample can enhance its fluidity, making the scope of application of the hydrogel wider.

Claims

1. An injectable hydrogel, characterized in that It is a chemically-physically cross-linked double network hydrogel constructed with a blend solution of magnesium acrylate, carboxymethyl chitosan and phytic acid as the main components. The covalent cross-links are derived from the polyacrylic acid network constructed by free radical polymerization, and the non-covalent cross-links are derived from the hydrogen bonds and electrostatic interactions between the components in the interpenetrating network, as well as the carboxymethyl chitosan chain entanglement network gradually induced by the salting-out effect, shielded electrostatic repulsion and enhanced hydrophobic chain interactions during application in the physiological environment; phytic acid forms more stable electrovalent bonds with proteins with the help of strong chelating ability; the dissipative matrix that is not easily affected by swelling and the multi-bonded adhesion interface cooperate to achieve long-term stable adhesion of the hydrogel in the physiological environment.

2. The method for preparing an injectable hydrogel according to claim 1, characterized in that: The following steps are involved: Step 1: Disperse magnesium hydroxide powder in deionized water, add acrylic acid solution, and react to prepare an aqueous solution of magnesium acrylate; Step 2: Add carboxymethyl chitosan powder and the prepared crosslinking agent solution to the aqueous solution of magnesium acrylate obtained in step 1, and stir well to prepare a carboxymethyl chitosan-crosslinking agent-magnesium acrylate aqueous solution; Step 3: Add a phytic acid solution with a concentration of 0-50 wt% and greater than 0 dropwise into the solution prepared in step 2, and stir for 10-40 minutes to obtain a hydrogel precursor solution; the mechanical strength of the hydrogel is regulated by adjusting the amount of phytic acid added; Step 4: Heat the precursor solution of the gel in step 3 in a water bath, add the prepared initiator solution dropwise, increase the temperature, and continue stirring until polymerization is completed to obtain a hydrogel. The adhesion strength of the hydrogel can be controlled by adjusting the content of magnesium acrylate, carboxymethyl chitosan, and crosslinking agent.

3. The method for preparing the injectable hydrogel according to claim 1, characterized in that: In the step 2, the concentration of the magnesium acrylate solution is 10-50 wt %; the degree of substitution of carboxymethyl chitosan is ≥80%, and the concentration is 1.0-5.0 wt %; the crosslinking agent is N, N′-methylenebisacrylamide, the solution concentration is 20 mg / mL, and the volume ratio of the crosslinking agent solution to the acrylic acid monomer solution is 0-1:8 and greater than 0.

4. The method for preparing the injectable hydrogel according to claim 1, characterized in that: In the step 4, the hydrogel precursor solution is heated at a temperature of 50-70° C. for 10-40 minutes; and the initiator is ammonium persulfate.

5. Use of the injectable hydrogel according to claim 1 as a rapid hemostatic material.

6. Use of the injectable hydrogel according to claim 1 as a tissue adhesion material under physiological conditions.

7. The use according to claim 5, characterized in that: The hydrogel is directly adhered to the surface of bleeding tissue.

8. The use according to claim 6, characterized in that: The hydrogel is directly adhered to the tissue surface to obtain a hydrogel-tissue adhesion interface that can function continuously in a physiological environment.

Citation Information

Patent Citations

  • Dual-network conductive hydrogel, preparation method thereof and flexible wearable electronic equipment

    CN114479125A

  • Preparation method and application of enzyme-regulated injectable alginate-based hydrogel

    CN118459795A

  • Skin adherent hydrogels

    US20050112151A1

Cited By

  • Sodium alginate / chitosan composite hydrogel as well as preparation method and application thereof

    CN121652414A